Acute Acute Oral Toxicity Study of Ethanol Extract of Cassava Peel (Manihot esculenta Crantz) on Male ddY Strain Mice (Mus musculus) - Ade Shinta Maria Br Napitu (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2025)
Background: The peel of cassava tuber (Manihot esculenta Crantz) is one of the plant materials known to contain active compounds with potential pharmacological activities. One such potential is its use as an antidiabetic agent, indicating the possibility of development into an herbal medicine. However, the safety level of cassava peel has not yet been established. Objective: To obtain information regarding the acute toxicity effects of ethanol extract of cassava tuber peel (Manihot esculenta Crantz), to determine its toxicity category, and to identify the LD₅₀ value of the ethanol extract in male ddY strain mice (Mus musculus). Methods: This study was an experimental research conducted in a laboratory setting using mice as test animals, employing the fixed dose method. Results: The results of the study showed that oral administration of ethanol extract of cassava tuber peel (Manihot esculenta Crantz) in male ddY strain mice (Mus musculus) did not produce symptoms of acute toxicity. Statistical analysis of all parameters showed that there was no significant difference between the normal group and the test group, with a p-value >0.05, indicating that there were no differences among all test animals.. Conclusion: The ethanol extract of cassava tuber peel (Manihot esculenta Crantz), when administered to mice, did not exhibit any acute toxic effects and is categorized as non-toxic with an LD₅₀ value greater than 5000 mg/kg body weight.